Use of Internet through Mobile Devices: A Survey - Shimray, Somipam R.; Ramaiah, Chennupati K. (Journal of Information and Knowledge, 2019)
The purpose of this paper is to examine the use of Internet through mobile devices. This study was conducted using a questionnaire. Findings reveal that most of the respondents admit the importance of the Internet in their day-to-day life. Over three fourths (79%) of them have access to the Internet on their mobiles and majority (84.8%) preferred accessing Internet at home.